General Practitioner Sentinel Network as a Tool of [Public] Health Surveillance - Rodrigues, Ana Paula (2016)
Current strategies of European health advocate the strengthening of the role of public health, requiring from decision-makers the ability to defend and enhance the health of individuals and populations in all policies. In the pursuit of this objective, public health should be evidence-based and so public health surveillance, seen as an important tool of public health since the nineteenth century, plays a central role in public health practice through the production and dissemination of the health information necessary for health planning and for evaluation of public health actions. Within the practice of public health estimations of disease frequency are important for outbreak control, health assessment, health needs assessment and estimation of health gains, but unfortunately these estimations are not always available for the entire population. In those cases and for diseases with high prevalence sentinel surveillance based in sentinel networks have some advantages for specific groups, namely needed of scarce resources and obtainment of quick results.The central role of family doctors in chronic disease management, their knowledge on individuals and families and their responsibilities in the management of a clear defined patients list are characteristics that make general practice an appropriate context to develop a sentinel network. In fact, in Portugal there is a general practitioner sentinel network named Rede Médicos-Sentinela working since 1989 which estimated, for the last 25 years, incidence rates of several chronic diseases, some of them targeted on national priority health programs. Thus, we consider that Rede Médicos-Sentinela can be integrated in a national surveillance system for chronic diseases in Portugal.